The Effect of Carbon Tax, Capital Expenditure and Firm Size on Carbon Emission Disclosure on the Indonesia Stock Exchange - Salmahabi Alliandra Putri; Apriani, Nuraida; Janiman (PT FORMOSA CENDEKIA GLOBAL, 2024)
The impacts of carbon tax, capital expenditure, and firm size on carbon emission disclosure are investigated and validated in this study. The focus of the research will be on industrial businesses with a mining related business that are listed between 2020 and 2022 on the Indonesia Stock Exchange (IDX). This study method use of purposive sampling. The secondary data used is financial records that are obtained from the Indonesia Stock Exchange website. The Eviews 12 program is used to do the panel data regression analysis. The results of the study indicate that carbon taxes are the only variables that significantly affect the disclosure of carbon emissions. Nonetheless, there are two different factors that negatively affect carbon emission disclosure: capital expenditure and firm size.